Structure-function relationships of the LRRC8 subunits and subdomains of the volume-regulated anion channel (VRAC) - Ghouli, Manolia R.; Fiacco, Todd A.; Binder, Devin K. (Frontiers in Cellular Neuroscience, 2022)
Volume Regulated Anion Channels (VRAC) are critical contributors to cell volume homeostasis and are expressed ubiquitously in all vertebrate cells. VRAC sense increases in cell volume, and act to return cells to baseline volume in a process known as regulatory volume decrease (RVD) through the efflux of anions and organic osmolytes. This review will highlight seminal studies that elucidated the role of VRAC in RVD, their characteristics as a function of subunit specificity, and their clinical relevance in physiology and pathology. VRAC are also known as volume-sensitive outward rectifiers (VSOR) and volume-sensitive organic osmolyte/anion channels (VSOAC). In this review, the term VRAC will be used to refer to this family of channels.